2015
DOI: 10.3109/14017431.2015.1013153
|View full text |Cite
|
Sign up to set email alerts
|

Association of thiol/disulfide ratio with syntax score in patients with NSTEMI

Abstract: TDR can be determined by an easy, inexpensive, automated, or optionally manual spectrophotometric assay, and correlates inversely with SXscore in patients with NSTEMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 26 publications
2
47
1
Order By: Relevance
“…32) In fact, similar to previous studies, we found that the native thiol level was decreased whereas the disulfide level and disulfide/total thiol ratio were increased in all study patients as a result of oxidative damage. 30,33,34) Based on these findings, we can speculate that thiol/disulfide homeostasis was also altered in cancer patients during anthracycline therapy.…”
Section: Discussionmentioning
confidence: 99%
“…32) In fact, similar to previous studies, we found that the native thiol level was decreased whereas the disulfide level and disulfide/total thiol ratio were increased in all study patients as a result of oxidative damage. 30,33,34) Based on these findings, we can speculate that thiol/disulfide homeostasis was also altered in cancer patients during anthracycline therapy.…”
Section: Discussionmentioning
confidence: 99%
“…An abnormality in this homeostasis results with a variety of disorders since thiol/ disulphide ratio play critical roles in antioxidant protection, detoxification, signal transduction, regulation of enzymatic activity, apoptosis and cellular signaling mechanisms. 7 Cigarette smoking involves some species which reacts with thiols and that inactivate enzymes whose function involves thiol groups. Thus damaging effect of smoking occurs via antioxidant depletion and thiol destruction .…”
Section: Introductionmentioning
confidence: 99%
“…These bonds may be reduced back to thiols, and thus thiol/disulphide homeostasis is sustained [8]. Recently it has been reported that the thiol/disulphide ratio is a novel oxidative stress marker, the level of which may alter in acute coronary syndromes [9,10]. Although there is a confirmed association of oxidative stress with atherosclerotic coronary heart disease, to our knowledge, there is no study that address thiol levels and thiol/disulphide homeostasis in stable CAD.…”
Section: Introductionmentioning
confidence: 99%